2019
DOI: 10.1038/s41598-019-40745-w
|View full text |Cite
|
Sign up to set email alerts
|

Electrocatalytic and Enhanced Photocatalytic Applications of Sodium Niobate Nanoparticles Developed by Citrate Precursor Route

Abstract: Development of cost effective and efficient electrocatalysts is crucial to generate H2 as an alternative source of energy. However, expensive noble metal based electrocatalysts show best electrocatalytic performances which acts as main bottle-neck for commercial application. Therefore, non-precious electrocatalysts have become important for hydrogen and oxygen evolution reactions. Herein, we report the synthesis of high surface area (35 m2/g) sodium niobate nanoparticles by citrate precursor method. These nano… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
51
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
3

Relationship

5
5

Authors

Journals

citations
Cited by 93 publications
(53 citation statements)
references
References 79 publications
(67 reference statements)
2
51
0
Order By: Relevance
“…As a photocatalyst active for the CO 2 conversion, CdS can also do its work when used as an electrocatalyst [57,63,68]. We report therein the literature's results obtained by the use of some potentially prebiotic metal sulfides as electrocatalyst for the CO 2 reduction, as they can be potentially active as photocatalysts [69,70], although careful experimental conditions tuning must be performed and discordant results can be obtained when shifting from electrocatalysis to photocatalysis and vice versa [71]. A study by Kitadai et al using various single-metal sulfides (Ag 2 S, CdS, CoS, CuS, FeS, MnS, MoS 2 , NiS, PbS, WS 2 , and ZnS) demonstrated that CdS and Ag 2 S function as excellent CO production catalysts [72].…”
Section: Sulfidesmentioning
confidence: 89%
“…As a photocatalyst active for the CO 2 conversion, CdS can also do its work when used as an electrocatalyst [57,63,68]. We report therein the literature's results obtained by the use of some potentially prebiotic metal sulfides as electrocatalyst for the CO 2 reduction, as they can be potentially active as photocatalysts [69,70], although careful experimental conditions tuning must be performed and discordant results can be obtained when shifting from electrocatalysis to photocatalysis and vice versa [71]. A study by Kitadai et al using various single-metal sulfides (Ag 2 S, CdS, CoS, CuS, FeS, MnS, MoS 2 , NiS, PbS, WS 2 , and ZnS) demonstrated that CdS and Ag 2 S function as excellent CO production catalysts [72].…”
Section: Sulfidesmentioning
confidence: 89%
“…The slurry was prepared by sonicating 2.5 mg of catalysts in 0.5 mL of isopropanol with 0.1 mL of Nafion solution for 10 min. Then a drop of the slurry was cast on the surface of glassy carbon and dried at 60 • C in vacuum oven [46,47]. The loaded amount of the nanoparticles was of~0.30 mg/cm 2 on the GC electrode, and the area of the working electrode was 0.07 cm 2 .…”
Section: Electrochemical Measurementsmentioning
confidence: 99%
“…Hence, to achieve good quantum efficiency in photocatalysis, the electron–hole pair separation efficiency and the ability of light utilization of the photocatalysts should be enhanced. 30–32 Thus, to increase the charge separation and spread the energy range of photoexcitation, the doping of foreign elements in semiconductor oxides is considered to be a suitable strategy. As a result of the doping, defects can be created in semiconducting oxides, such as trapped states and oxygen vacancies, which effectively inhibit the recombination of electron–hole pairs owing to the capturing of electrons alone, thus improving the performances of metal oxides in photocatalysis.…”
Section: Introductionmentioning
confidence: 99%